A case report: gastric adenocarcinoma in childhood - Aydoğan, Ayşen; Corapçioğlu, Funda; Elemen, E Levent; Tugay, Melih; Gürbüz, Yeşim; Oncel, Selim (The Turkish Journal of Pediatrics, 2009)
Primary gastric adenocarcinoma is extremely rare in children, and accounts for 0.05% of all gastrointestinal malignancies during childhood. The initial symptoms of epigastric pain, feeling of fullness, belching, and loss of appetite are non-specific and misleading. Nausea, vomiting and weight loss may accompany, which also complicate reaching a prompt diagnosis. In the presented case, a 15-year-old girl admitted with ascites, pleural effusion, right supra-clavicular lymphadenopathy, and back pain. No primary focus of a malignancy was accomplished in radiological evaluation, and the diagnosis of gastric carcinoma was achieved with upper gastrointestinal system endoscopy. We point out the importance of upper gastrointestinal system endoscopy in patients with ascites and uncertain diagnosis of the primary focus of malignancy.